Cognitive ability and economic growth: how much happiness is optimal? - Nik Ahmad Sufian Burhan; Mohamad Fazli Sabri; Heiner Rindermann (International Review of Economics, 2022)
The cognitive human capital approach assumes that cognitive abilities (CA) enable societies to be innovative and competitive and to achieve higher productivity and prosperity. However, does happiness enhance the effect of CA on economic growth? Our study views happiness as an intrinsic motivator that helps workers be more productive and get the most out of their CA. Regression analyzes using two different measures for CA showed strong evidence that CA generated economic growth from 1960 to 2017, even though it interacted negatively with happiness. These results were found to be robust after controlling for endogeneity bias using instrumental variable for happiness. In addition, the threshold regression analyses revealed significant evidence that the relationships between CAs and growth vary according to happiness levels. Two prominent ranges of threshold were established: γ10.167em=0.167em4.75–4.96 and γ20.167em=0.167em6.16–6.43 on the 0 to 10 happiness scale. Accordingly, the effects of CA were smallest in very unhappy countries (happiness0.167em<0.167emγ1), strongest in fairly happy societies (happiness of γ10.167em-0.167emγ2), and moderately strong among the happiest countries (happiness0.167em≥0.167emγ2). In summary, the pursuit of highest productivity growth seems to require an optimal level of happiness, where moderate level of happiness (likely indicative of existence of higher motivation with little emotional distress) could inspire and drive people to fully utilize their cognitive capital and achieve high economic growth.
Keywords: J24; E71; O47; B52; 330; Cognitive ability; Economic growth; Happiness; Human motivation; Savanna-IQ interaction hypothesis